Impact of Youth Migration on the Agricultural Sector in Nepal - Timsina, Tirtha Raj (Rupantaran: A Multidisciplinary Journal, 2024)
The paper examines the impact of youth migration on the agricultural sector in Nepal. Nowadays, youth are involved in both internal and international migration to seek better income opportunities and secure living conditions. The increasing trend of youth migration is significantly affecting the agricultural sector by transforming knowledge and skills through the adoption of agricultural technology, the selection of profitable crops, increasing productivity, increasing food security, and exporting crops. The paper follows descriptive research method and based on secondary data sources like scholarly articles, journals, and authentic reports to analyze qualitative and quantitative information. It concludes that youth migration is a significant issue, despite potential negative impacts in developing countries like Nepal. Migration boosts household income through remittances but can lead to labor shortages, land loss, and decreased productivity. Negative effects include increased reliance on remittance earnings and a deteriorating working attitude.